Apple Location Method for the Apple Harvesting Robot - Wenhua Mao; Baoping Ji; Jicheng Zhan; Xiaochao Zhang; Xiaoan Hu (2009 2nd International Congress on Image and Signal Processing, 2009)
The apple harvesting robot should have two eyes to sensor the location of picking apples. The binocular machine vision system used two Canon digital cameras was built, instead of digital video used as usual. Thus, the digital camera vision system had higher resolution and superior performance than a digital video vision system, which could capture a Jpeg image with 3456*2592 pixels, its field of view included the whole apple tree. For the Fuji apple tree, it is an obvious color difference with ripe apples and their surroundings of leaves and braches. Therefore, the Drg-Drb color index was used to segment apples from their surroundings. Then the mistaken classified background regions was deleted by the area filter, and he picking apples were similarly chosen by area parameter. After that, the conglutinated apples were segmented by the bidirectional scanning line algorithm, which were scanned from the horizontal and vertical direction. Finally, all of picking apples were positioned by their circum-diameter matching algorithm. The experimental result showed that the correct classification rate of picking apple fruit achieved 90%.